2021
DOI: 10.1055/s-0041-1723099
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Physician-Based Stroke Unit in a Remote Hospital of North-East India-Tezpur Model

Abstract: Objective The study aims to determine the effects of implementing stroke unit (SU) care in a remote hospital in North-East India. Materials and Methods This before-and-after implementation study was performed at the Baptist Christian Mission Hospital, Tezpur, Assam between January 2015 and December 2017. Before the implementation of stroke unit care (pre-SU), we collected information on usual stroke care and 1-month outcome of 125 consecutive stroke admissions. Staff was then trained in the delivery of SU care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…External to this review, expert opinion provided in other articles regards multidisciplinary SUs to be a gold standard in stroke care with numerous bene ts. 4,20,21 A key strength of the "train-the-trainer" approach is potential sustainability -the Indian study by John et al (2021) 17 and Wessex-Ghana 14 study by Johnson et al (2017) demonstrated that healthcare professionals can educate their co-workers upon training, and the Wessex-Ghana Stroke Partnership has appointed deputies to support clinical leaders with the aim of succession planning. Furthermore, while a train-the-trainer approach may be effective and implemented with existing human resources, successful approaches, such as in the Wessex-Ghana Stroke Partnership, have involved signi cant input from external healthcare expert professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…External to this review, expert opinion provided in other articles regards multidisciplinary SUs to be a gold standard in stroke care with numerous bene ts. 4,20,21 A key strength of the "train-the-trainer" approach is potential sustainability -the Indian study by John et al (2021) 17 and Wessex-Ghana 14 study by Johnson et al (2017) demonstrated that healthcare professionals can educate their co-workers upon training, and the Wessex-Ghana Stroke Partnership has appointed deputies to support clinical leaders with the aim of succession planning. Furthermore, while a train-the-trainer approach may be effective and implemented with existing human resources, successful approaches, such as in the Wessex-Ghana Stroke Partnership, have involved signi cant input from external healthcare expert professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Training the Trainer for the Implementation of Multidisciplinary Stroke Units An Indian pre/post implementation study used a "train-the-trainer" approach to implement a stroke unit (SU). 17 The trainer (one physician) was trained by local experts for two hours via video conference (Skype), three times a week for four weeks. The trainer then conducted two-hour training sessions with healthcare professionals in nursing, physiotherapy, and occupational therapy for ve days per week over four weeks.…”
Section: Identi Cation Of Themesmentioning
confidence: 99%
“…Strengthening the stroke care systems requires a multidisciplinary approach, which includes dedicated infrastructure by training the ambulance crew, physician, nurses, and therapists to implement protocol-driven care [26]. Establishing stroke units in district-level hospitals will help improve key indicators like in-hospital secondary stroke prevention, swallowing assessment, mobility, and re-education [27]. Moreover, providing intravenous rtPA free of cost or by insurance coverage using the hub-and-spoke structure model can increase the thrombolysis rate [28].…”
Section: Discussionmentioning
confidence: 99%
“…10 A successful implementation of the non-specialist model was illustrated in Tezpur district, a remote area of Northeast India with improvements in quality measures and reductions in in-hospital complications. 11 Advances in technology can facilitate both training of nonspecialists and stroke care delivery. For example, telestroke offers the opportunity to provide stroke care in locations deprived of specialists physically on-call.…”
Section: Introduction and Rationalementioning
confidence: 99%